2002
DOI: 10.1046/j.1365-8711.2000.03760.x
|View full text |Cite
|
Sign up to set email alerts
|

Asteroids in the inner Solar system - I. Existence

Abstract: Ensembles of in‐plane and inclined orbits in the vicinity of the Lagrange points of the terrestrial planets are integrated for up to 100 Myr. The integrations incorporate the gravitational effects of the Sun and the eight planets (Pluto is neglected). Mercury is the least promising planet, as it is unable to retain tadpole orbits over 100‐Myr time‐scales. Mercurian Trojans probably do not exist, although there is evidence for long‐lived, corotating horseshoe orbits with small inclinations. Both Venus and the E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 36 publications
6
76
3
Order By: Relevance
“…Especially for the Earth case, the close encounters decrease the inclination in such a way that the Hungarias enter the window of stability for the Earth co-orbital objects as shown in Tabachnik & Evans (2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for the Earth case, the close encounters decrease the inclination in such a way that the Hungarias enter the window of stability for the Earth co-orbital objects as shown in Tabachnik & Evans (2000).…”
Section: Discussionmentioning
confidence: 99%
“…3 let us see multiple close approaches to Mars and after that also to the Earth. In the time-span between about 55 Myr and 65 Myr of integration, many close encounters are found, thus the inclination change dramatically and that leads to the Earth asteroids capture: the orbital elements of the captured asteroid lies in the stability window for that planet as shown by Tabachnik & Evans (2000).…”
Section: Orbital Evolution Of a Typical Hco And Transport Mechanismmentioning
confidence: 99%
“…• away from Earth in mean anomaly (Tabachnik & Evans 2000), they spend most of their time in regions of the sky that are difficult or impossible for ground-based telescopes to observe. Infrared measurements from NEOWISE have provided preliminary estimates of diameters and albedos .…”
Section: Earth Co-orbitalsmentioning
confidence: 99%
“…In Mikkola & Innanen (1992) and Zhang & Innanen (1995) the authors found that Venus, Earth, and Mars can host co-orbital asteroids up to 10 Myr. According to the investigation of Tabachnik & Evans (2000), Earth's Trojans are on stable orbits when their inclinations are relatively low (i < 16…”
Section: Introductionmentioning
confidence: 99%